Development of high frequency generator for bipolar electrosurgical unit - Idham alzaidi, Ali; yahya, Azli; Tian Swee, Tan; Idris, Norhalimah (International Journal of Engineering and Technology, 2018)
Power Electronics is widely used in bioscience and medical instruments such as Electrosurgical Units, MRI and X-ray. An advance development in switch mode power supply leads to a new design topology of DC to DC convertor for Electrosurgical Systems. The new designed system has a capacity to produce high efficient output power with high resonance, this improves the performance of the surgery operation. This paper reports a Buck-Boost topology DC to DC (Flyback) converter with high power switching. The simulation results show an improved performance when compared to the existing system.Â